"Munera Gladiatoria" and Female Gladiators in the Ancient World = "Munera Gladiatoria" i gladiatorki w świecie antycznym - Gatti, Angela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In recent years, the phenomenon of female gladiators has received much scholarly attention (McCullough 2008, Manas 2011, Miączewska 2012, Brunet 2014, Kocjan 2018). Some issues, however, remain unresolved, especially as regards the importance of the event in ancient Rome, its frequency, and its characteristics. The aim of this study is to offer new insights on the problem, starting from a careful analysis in chronological order of all the ancient sources that have reported the phenomenon and commented on the presence of women in the arena. In the second part of the paper, I analyse the archaeological and epigraphic evidence, although fewer in number than the literary ones. In this way, I will try to recreate a picture of the situation as complete as possible.
Keywords: female gladiators; female gladiation; female fights; "munera gladiatoria"; gender studies; gladiatorki; walki kobiet